‘Ap Lisurug’ Mekanisme Pertukaran Babi dalam Budaya Yali - Peyon, A Ibrahim (Universitas Cenderawasih, 2023)
This article describes pig exchange parties in the Yali people in the Highlands of New Guinea. This study aims to describe activities related to pig exchange mechanisms, processes, meanings, and values. This study used a descriptive method of participation with observation techniques, direct participation, and in-depth interviews with key informants involved in planning, leading, and conducting these activities. The Method of analysis identifies the value, meaning, and purpose of the activity. The results described that this activity is an important dance party for the community as a mechanism for exchanging pigs with many other cultural values. The meanings and values found are economic values that include exchanging pigs and eating pork together, social values related to togetherness, kinship, and marriage relationships, political values to improve social status, strengthen solidarity, eliminate fatigue from various activities, and increase new spirit expressed through song and dance, as well as many other aspects.